Evaluasi Usability Aplikasi Zoom Meeting menggunakan System Usability Scale - Anwar Sodik; Rahmi Rizkiana Putri (Institut Teknologi Adhi Tama Surabaya, 2021)
Zoom Meeting has become a top-rated application in the past year. Pandemic forces almost everyone in the world to work from home. Zoom Meeting is one of the meeting applications widely used by the public; it is necessary to carry out a usability test process. SUS is an evaluation method used to see the reusability of a product. The evaluation was carried out on 20 respondents who used Zoom Meeting with a usage intensity of more than 20 hours each week. The results of the SUS evaluation obtained a score of 78.4 with a grade of